2018
DOI: 10.1002/jat.3746
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium compounds and cellular death mechanisms in the A549 cell line: The relevance of the compound valence

Abstract: Non‐small lung cell carcinoma has a high morbidity and mortality rates. The elective treatment for stage III and IV is cisplatinum that conveys serious toxic side effects. Vanadium compounds are metal molecules with proven antitumor activity that depends on its valence. Therefore, a better understanding of the mechanism of action of vanadium compounds is required. The aim of our study was to investigate the mechanisms of cell death induced by sodium metavanadate (NaVO3 [V(+5)]) and vanadyl sulfate (VOSO4 [(+4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…However, the higher ROS level was induced by complexes containing vanadium(+IV) in the coordination center [46]. These results suggest that the efficacy of the ROS generation induced by vanadium compounds depends on the oxidation state of the vanadium cation presented in the coordination sphere of the complex [46]. For peroxovanadate complexes, the results are consistent.…”
Section: Oxidative Stressmentioning
confidence: 52%
See 3 more Smart Citations
“…However, the higher ROS level was induced by complexes containing vanadium(+IV) in the coordination center [46]. These results suggest that the efficacy of the ROS generation induced by vanadium compounds depends on the oxidation state of the vanadium cation presented in the coordination sphere of the complex [46]. For peroxovanadate complexes, the results are consistent.…”
Section: Oxidative Stressmentioning
confidence: 52%
“…In one of the most recent studies, vanadium salts, sodium metavanadate NaVO 3 (36) and vanadium(IV) sulfate oxideVOSO 4 (37) significantly increased the ROS level in human lung cancer cells. However, the higher ROS level was induced by complexes containing vanadium(+IV) in the coordination center [46]. These results suggest that the efficacy of the ROS generation induced by vanadium compounds depends on the oxidation state of the vanadium cation presented in the coordination sphere of the complex [46].…”
Section: Oxidative Stressmentioning
confidence: 87%
See 2 more Smart Citations
“…Studies in vivo and in vitro showed that vanadium compounds induce cell death in leukemia [21], lung cancer [22] cervical and breast carcinoma [23], neuroblastoma [24], liver carcinoma [25], osteosarcoma [26], and pancreatic ductal adenocarcinoma [27]. In vitro studies demonstrated that the cell lines stimulated with vanadium compounds produce H 2 O 2 and O 2 and induce autophagy, necroptosis, and mitotic catastrophe [27].…”
Section: Oxidative Stress Vanadium and Cellular Deathmentioning
confidence: 99%